Advances in Defining Ecosystem Functions of the Terrestrial Subsurface Biosphere - Meyer-Dombard, D’Arcy R.; Malas, Judy (Frontiers in Microbiology, 2022)
The subsurface is one of the last remaining ‘uncharted territories’ of Earth and is now accepted as a biosphere in its own right, at least as critical to Earth systems as the surface biosphere. The terrestrial deep biosphere is connected through a thin veneer of Earth’s crust to the surface biosphere, and many subsurface biosphere ecosystems are impacted by surface topography, climate, and near surface groundwater movement and represent a transition zone (at least ephemerally). Delving below this transition zone, we can examine how microbial metabolic functions define a deep terrestrial subsurface. This review will provide a survey of the most recent advances in discovering the functional and genomic diversity of the terrestrial subsurface biosphere, how microbes interact with minerals and obtain energy and carbon in the subsurface, and adaptations to the presented environmental extremes. We highlight the deepest subsurface studies in deep mines, deep laboratories, and boreholes in crystalline and altered host rock lithologies, with a focus on advances in understanding ecosystem functions in a holistic manner.